Inhibition of VE-PTP rejuvenates Schlemm’s canal in aged mice and acts via Tie2 - Sarthak Mishra; Ute Ipe; Astrid F. Nottebaum; Kevin G. Peters; Dietmar Vestweber (PLoS ONE, 2025)
Purpose Glaucoma is the leading cause of irreversible blindness worldwide and is associated with high intraocular pressure (IOP). Schlemm’s canal (SC), a hybrid vessel present in the anterior part of the eye, is known to control IOP by draining aqueous humor into the systemic circulation. Formation and function of SC is supported by the tyrosine kinase receptor Tie2. Likewise, inhibition of the vascular endothelial protein tyrosine phosphatase (VE-PTP), which associates with Tie2 has similar effects. However, VE-PTP also targets VE-cadherin and several other substrates. Here, we analyzed whether Tie2 is indeed the major substrate which is responsible for the role of VE-PTP in SC function. In addition, we analyzed the function of VE-PTP in SC of the aged eye in mice. Methodology We tested the effects of the VE-PTP inhibitor AKB9778 and of VE-PTP gene inactivation on SC area and IOP in WT and in Tie2iLEC/SC-KO and VE-cadherin-Y685F mutant mice. Results Pharmacologic inhibition of VE-PTP with AKB9778 increased SC area only in mice expressing Tie2. The VE-cadherin-Y685F mutation had neither an effect on SC area nor on the effects of AKB9778 on SC formation. Induced VE-PTP gene inactivation in adult mice had similar effects as AKB9778. Furthermore, we could show that AKB9778 improved SC function in aged mice as judged by increasing SC area and lowering of IOP. Conclusion Interference with VE-PTP function improves SC function in a strictly Tie2 dependent way and pharmacologic inhibition of VE-PTP with AKB9778 is a promising approach for improving SC function in the aged eye.